Pelaksanaan Metode Pembelajaran Partisipatif (Partisipatory learning) Dalam Meningkatkan Keaktifan Siswa Pada Mata Pelajaran Akidah Akhlak Di Kelas X IPS Madrasah Aliyah Pondok Pesantren KH. Ahmad Dahlan Teluk Kuantan - Mas Ihwan Rida; Bustanur Bustanur; Ikrima Mailani (Universitas Islam Kuantan Singingi, 2020)
MAS IHWAN RIDA, “ The Implementasi of Partisipatory Learning in Improving Students Activeness on The Subject of Akidah Akhlak in 1st grade Students of Sosial Islamic Senior High School of K.H Ahmad Dahlan Teluk Kuantan”. 2019 The Student of Faculty Tarbiiyah and faculty of teacher and Education Islamic University of Kuantan Singingi. The implementation of learning methods in the learning process was an easy way to achieve a learning goals. In the other hand, for the success of learning process it was needed to pay attention that what the learning methods used, therefore the material which was given was more easy to absorbed or easy for students to understand. Therefore, the aim of this research were : 1) How The Implementasi of Partisipatory Learning in Improving Students Activeness on The Subject of Akidah Akhlak in 1st grade Students of Sosial Islamic Senior High School of K.H Ahmad Dahlan Teluk Kuantan, 2) The factors which was influencing The Implementasi of Partisipatory Learning in Improving Students Activeness on The Subject of Akidah Akhlak in 1st grade Students of Sosial Islamic Senior High School of K.H Ahmad Dahlan Teluk Kuantan. Based on the analysis the writer’s research of The Implementasi of Partisipatory Learning in Improving Students Activeness on The Subject of Akidah Akhlak in 1st grade Students of Sosial Islamic Senior High School of K.H Ahmad Dahlan Teluk Kuantan, was increased, before an action occurs, the percentage was 61,1%, in cycle I was 72,9%, and cycle II was increased 81,4%.The factors which was influencing a model Aptitude Treatment Interaction in improving students Learning Achievement 0f 5th grade Student on the subject of Aqidah Akhlak in Muhammadiyah Islamic Elementary School Teluk Kuantan, there were: 1. Students internal factors ( student personal factors ), 2. Enviromental factors. 3. Communication factors. Keywords : The Implementasi of Partisipatory Learning and Students Activeness